SIKAP CHINA TERHADAP PERJANJIAN TRANS-PACIFIC PARTNERSHIP China’s Reaction Toward The Trans-Pacific Partnership - Lucky Dwi Fitriany (HI 16 UMY 159, 2016)
*159 China is the country with the largest economy in Asia. the rise of China, which grew rapidly to make the United States as a superpower concerned position will be replaced by China. thesis will discuss about the dominance of China in the Asia Pacific region received a response by the United States to encourage the Trans-Pacific Partnership agreement is finally reached an agreement on October 5, 2015 in Atlanta, Georgia, United States. This agreement has the purpose to liberalize Trafficking in the Asia Pacific region and been anticipated would provide substantial economic gains for the member states because it covers 40% of the total GDP of the world. However, although China received an invitation to join this agreement, China still consider very carefully the decision to join or not. in this thesis, the theory that describes the state used China as a rational actor who consider all gains and losses on all decisions. of analysis using the existing theories, it will find out how the attitude of China with this agreement.